Integrasi pembelajaran kolaboratif yang didukung aplikasi pembelajaran seluler: tinjauan dalam kasus pendidikan tinggi - Dailami Firdaus; Masduki Ahmad; Reni Armiati (Akademika : Jurnal Teknologi Pendidikan, 2024)
Integration of mobile learning application-supported collaborative learning: review in higher education case. This study aims to determine: 1) Mobile applications in collaborative learning in higher education; 2) Integration of mobile applications in learning in higher education; 3) How the influence of application integration factors on learning in higher education. This study uses a literature review system to obtain articles by selecting titles and contexts. The articles obtained and analyzed were as many as 30 articles. Furthermore, advanced data is presented by grouping the applications, educational subjects, and research methods. The results show: 1) There are six types of mobile applications in use, namely social media, cloud, mobile app, MOOCS, web, and LMS; 2) Integration learning is carried out by selecting applications that can support collaborative learning, dividing student groups, utilizing available features to deliver learning; 3) The positive influence of mobile learning on collaborative learning is 90%. Based on the research results, lecturers in higher education can use the following recommendations: Implementation of collaborative learning can be done with various types of mobile applications. Educators are advised only to use mobile applications that contain text communication and image sending. When choosing a mobile application, it is recommended to consider learning objective and utilize the available features to deliver learning.